1989
DOI: 10.1021/bi00442a015
|View full text |Cite
|
Sign up to set email alerts
|

Salt effects on histone subunit interactions as studied by fluorescence spectroscopy

Abstract: The salt concentration dependence of the aggregation properties of calf thymus and chicken erythrocyte histones has been investigated by using fluorescence spectroscopy. The isolated H2A/H2B and H3/H4 subunit preparations were labeled with 5-(dimethylamino)naphthalene-1- sulfonyl (dansyl). This long-lived fluorescence probe allows for the observation of rotations due to tumbling of the particle and thus is a probe for changes in the size of macromolecular assemblies. The fluorescence polarization and lifetime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Lowering the salt concentration to 200 mM slightly stabilized the protein to 6 X 10~8 M. Our data indicate a small negative volume change for the dissociation of the core particle octamer. The (H3)2(H4)2 tetramer, as was shown in the previous paper (Royer et al, 1989), also formed predominantly dimers of tetramers at higher protein or salt concentrations. In the study presented here, we found the dissociation constant for the H3/H4 octamer to dimer transition to be 1 X 10~21 M3 ***(Cly-2 = 4 X 10~8 M) at 2 M NaCl for the CT preparation.…”
supporting
confidence: 79%
“…Lowering the salt concentration to 200 mM slightly stabilized the protein to 6 X 10~8 M. Our data indicate a small negative volume change for the dissociation of the core particle octamer. The (H3)2(H4)2 tetramer, as was shown in the previous paper (Royer et al, 1989), also formed predominantly dimers of tetramers at higher protein or salt concentrations. In the study presented here, we found the dissociation constant for the H3/H4 octamer to dimer transition to be 1 X 10~21 M3 ***(Cly-2 = 4 X 10~8 M) at 2 M NaCl for the CT preparation.…”
supporting
confidence: 79%
“…Moreover, the apparent Stokes diameter obtained from the fits increased with the time of equilibration over a time scale of tens of minutes, ultimately reaching values that were significantly in excess of that determined for the octamer itself. It is known that the H2A-H2B heterodimers and the H32H42 tetramers produced by dissociation of histone octamers can form unnatural aggregates in approximately physiological ionic strength (Baxevanis et al, 1991;Royer et al, 1989;Scarlata et al, 1989;Sperling & Bustin, 1975; van Holde, 1989). We suspected that some of the heterodimers or tetramers or both might be polymerizing over time and that the autocorrelation functions obtained included contributions from both aggregates and any remaining heterodimers and tetramers.…”
Section: Resultsmentioning
confidence: 99%
“…An important attribute of this model is that it allows for maintenance of a relationship between regulatory signals encoded in the form of posttranslational histone modifications (van Holde, 1989;Wassarman & Kornberg, 1989) and the underlying DNA sequence. However, histone octamers are unstable in physiological ionic conditions; at equilibrium, octamers dissociate into an H3jH42 tetramer and two H2A-H2B heterodimers (Thomas & Butler, 1977; van Holde, 1989;Wassarman & Kornberg, 1989), and these in turn can repolymerize into nonnative H3-H4 or H2A-H2B polymers (Baxevanis et al, 1991;Royer et al, 1989;Scarlata et al, 1989;Sperling & Bustin, 1975; van Holde, 1989). If histone octamers were to dissociate during the time scale of polymerase progression, they would not be able to re-form a nucleosome after the polymerase had passed by.…”
mentioning
confidence: 99%
“…FP has also been used to study the dynamics of monomer/dimer formation . Royer et al have studied the effect of salt concentration on histone subunit interactions using fluorescence polarization …”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Royer et al have studied the effect of salt concentration on histone subunit interactions using fluorescence polarization. 28,29 Self-interaction chromatography (SIC) is a technique that can provide information about the self-interactions of a given protein, the second virial coefficient (B 22 ) and the effect of mobile phase modifiers on these interactions. 30 Cross interaction chromatography (CIC) is a modified form of SIC which enables one to study weak interactions between two different proteins.…”
Section: Introductionmentioning
confidence: 99%